Restoring the impaired cardiac calcium homeostasis and cardiac function in iron overload rats by the combined deferiprone and N-acetyl cysteine - Suwakon Wongjaikam (2018)
© 2017 The Author(s). Intracellular calcium [Ca 2+ ] i dysregulation plays an important role in the pathophysiology of iron overload cardiomyopathy. Although either iron chelators or antioxidants provide cardioprotection, a comparison of the efficacy of deferoxamine (DFO), deferiprone (DFP), deferasirox (DFX), N-acetyl cysteine (NAC) or a combination of DFP plus NAC on cardiac [Ca 2+ ] i homeostasis in chronic iron overload has never been investigated. Male Wistar rats were fed with either a normal diet or a high iron (HFe) diet for 4 months. At 2 months, HFe rats were divided into 6 groups and treated with either a vehicle, DFO (25 mg/kg/day), DFP (75 mg/kg/day), DFX (20 mg/kg/day), NAC (100 mg/kg/day), or combined DFP plus NAC. At 4 months, the number of cardiac T-type calcium channels was increased, whereas cardiac sarcoplasmic-endoplasmic reticulum Ca 2+ ATPase (SERCA) was decreased, leading to cardiac iron overload and impaired cardiac [Ca 2+ ]i homeostasis. All pharmacological interventions restored SERCA levels. Although DFO, DFP, DFX or NAC alone shared similar efficacy in improving cardiac [Ca 2+ ]i homeostasis, only DFP + NAC restored cardiac [Ca 2+ ]i homeostasis, leading to restoring left ventricular function in the HFe-fed rats. Thus, the combined DFP + NAC was more effective than any monotherapy in restoring cardiac [Ca 2+ ] i homeostasis, leading to restored myocardial contractility in iron-overloaded rats.